ANALISIS DAMPAK PENERAPAN IFRS 17 PADA RISIKO ASURANSI DAN NILAI PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA EMITEN ASURANSI DI BURSA EFEK INDONESIA - Ni Ketut Melinda Dewi Utami; Ni Luh Kardini (Nusantara Hasana Journal, 2024)
This study aims to analyze the effect of insurance risk, firm value, and IFRS 17 implementation on the financial performance of insurance issuers listed on the Indonesia Stock Exchange (IDX) during the 2022-2023 period. Secondary data is obtained from the financial statements of insurance companies listed on the IDX. The analysis method used is multiple linear regression with the Eviews 12 tool. The results showed that insurance risk (sig. 0.000) and firm value (sig. 0.000) had a significant positive effect on financial performance. In addition, the application of IFRS 17 is also proven to have a significant positive effect on financial performance (sig. 0.045). Simultaneously, insurance risk, firm value, and IFRS 17 also have a significant positive effect on the financial performance of insurance issuers (sig. 0.000). The implication of this study is that insurance companies need to pay attention to risk management, increase firm value, and implement IFRS 17 properly to achieve optimal financial performance.